2016
DOI: 10.1097/md.0000000000005760
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib followed by autologous stem cell transplantation in a patient with rheumatoid arthritis

Abstract: Rationale and Patients concerns:Despite the introduction of varied disease-modifying antirheumatic drugs and biological agents, a substantial proportion of patients remain untreatable. We report a 56-year-old Chinese female patient with a case of refractory rheumatoid arthritis (RA) complicated with multiple myeloma (MM) who was treated successfully with Bortezomib followed by autologous stem cell transplantation (ASCT).Diagnosis and Interventions:We report a 56-year-old Chinese female patient who was diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We and others have shown that BZ, at very low nontumor-suppressive doses, can modulate immune cell activation (28,29). Recent clinical studies demonstrated that BZ is an effective immunomodulatory therapy for arthritis, transplant rejection, graft-versus-host disease, and autoimmune diseases (30)(31)(32)(33)(34). BZ appears to be a safe immunomodulatory drug with a very favorable side effect profile (35).…”
Section: Genetic Damping Of Myeloid Activation Ameliorates Iso-induce...mentioning
confidence: 99%
“…We and others have shown that BZ, at very low nontumor-suppressive doses, can modulate immune cell activation (28,29). Recent clinical studies demonstrated that BZ is an effective immunomodulatory therapy for arthritis, transplant rejection, graft-versus-host disease, and autoimmune diseases (30)(31)(32)(33)(34). BZ appears to be a safe immunomodulatory drug with a very favorable side effect profile (35).…”
Section: Genetic Damping Of Myeloid Activation Ameliorates Iso-induce...mentioning
confidence: 99%
“…However, bortezomib also significantly improved general symptoms in pSS patients, particularly fatigue, reduced serum globulin levels, and serum viscosity, according to previous reports [ 47 ]. In both animal experiments and clinical trials, bortezomib ameliorated symptoms after the first cycle and continued to improve gradually in patients with refractory RA [ 48 ]. In addition, we also predicted protease inhibitors, such as carfilzomib, oprozomib, and marizomib, as candidate drugs for the treatment of RA and pSS.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, delanzomib, a novel proteasome inhibitor, was successfully used together with adalimumab in a rat model of rheumatoid arthritis [ 147 ]. Moreover, two case reports showed remission of rheumatoid arthritis complicated with multiple myeloma [ 148 ] or TEMPI syndrome [ 149 ] after administration of bortezomib.…”
Section: Discussionmentioning
confidence: 99%